Agriculture extension in Viet Nam: An assessment and reform options - Ngan, Pham Hoang; Babu, Suresh Chandra (International Food Policy Research Institute, 2018)
In 2015, Viet Nam began transforming its agriculture extension and advisory services to improve the efficiency and competitiveness of its agricultural sector and thus improve the livelihoods of its farmers. Despite these recent efforts, however, farmers continue to face many challenges and constraints. This paper evaluates the performance of the current extension and advisory system, identifies challenges faced, and analyzes constrains and opportunities for further reforms. Finally, it provides recommendations for both policy makers and practitioners regarding possible improvements in extension and advisory services in Viet Nam by focusing on contextual factors as well as the performance and quality of the extension services being provided.